Dynamics of Family Disharmony Without Offspring from The Perspective of Maqāṣid Al-Sharī'ah and its Implications for Household Resilience (A Case Study in Ketapang Village, Sungkai Selatan District, North Lampung Regency) - Riyadus Shalihin; Habib Sulthon Asnawi; Iwannudin Iwannudin (Assyfa Journal of Islamic Studies, 2026)
The presence of children in a family has a strategic function as a continuation of lineage, heir to traditions, and outpouring of affection. However, not all couples are blessed with children. The absence of children has the potential to create dynamics of disharmony that threaten household resilience. This study aims to analyze the factors influencing disharmony in childless families, its implications for household resilience, and solutions based on maqashid sharia. The research employs a qualitative method with a phenomenological approach in Ketapang Village, North Lampung. Data were collected through in-depth interviews with three couples who have been married for more than eight years without children, participant observation, and documentation. The findings indicate that internal factors (weak religious foundation, lack of role models, and non-comprehensive application of Islamic values) and external factors (social pressure and lack of family support) contribute to disharmony. Negative impacts include infidelity, chronic quarrels, and divorce. Maqashid sharia-based solutions include the protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-aql), lineage (hifz al-nasl), and property (hifz al-mal). This research confirms that family harmony without children can be achieved through strengthening spirituality, effective communication, and constructive social support.